Native blue elderberry in hedgerows bridges revenue and conservation goals - Sonja Brodt; Gwenael Engelskirchen; Katie Fyhrie (California Agriculture, 2024)
Field edge hedgerows have long been promoted by UC Cooperative Extension and other organizations as a way to bring needed biodiversity to California farms. However, adoption of hedgerow planting still falls far short of available edge capacity. Our study explores a new multifunctional model of hedgerows that combines production with environmental conservation goals by considering the revenue potential of harvesting blue elderberry. Blue elderberry is a drought-tolerant native species well adapted to multiple microclimates in California and the western United States. The growth of elderberry herbal products and specialty foods markets is currently skyrocketing nationally and globally, and blue elderberry may offer a promising entry into these markets. Blue elderberry is also sought out by Indigenous people as one important component in efforts to restore cultural and food sovereignty. A field demonstration trial in the southern Sacramento Valley found that elderberry yields from 1,000-foot-long multi-species hedgerows could potentially provide from $2,000 to $3,000 in net annual revenue within 3 to 5 years, with much more possible as the hedgerows mature.